Agda desmontagem: o de dentro da cena - Hilda Hilst e os femininos que ressoam - Gisele Petty (2022)
This dissertation deals with the disassembly of the theatrical show Agda (2004), created from the homonymous short story by Hilda Hilst (1973). Disassembly is a practice that was born in the context of the Latin American theater scene of the 1990s at Eitalc - International Theater School of Latin America and the Caribbean, and consists of revisiting a previously created theatrical show from the perspective of subjectivities and materialities of composition from the actresses and creative actors. The methodological strategies applied here, considered the pedagogical and performative aspect that disassembly installs. Therefore, the course of this research was a writing affected by practice, present in scenic experiments that followed the process over these two years. The word in this work is almost always female: Hilda, Agda, women who disassemble the theatrical scene in Brazil, the Latin American actresses who inspire us, the actresses who inspired them. Research can scatter seeds and they are grains of corn and wheat, gifts from a Goddess ruling a soil from before.